2018
DOI: 10.1302/0301-620x.100b9.bjj-2018-0031.r2
|View full text |Cite
|
Sign up to set email alerts
|

A six-year observational study of 31 children with early-onset scoliosis treated using magnetically controlled growing rods with a minimum follow-up of two years

Abstract: The progression of EOS can be controlled using MCGRs allowing growth and improved function. Younger and syndromic children are more likely to develop complications following surgery. Cite this article: Bone Joint J 2018;100-B:1187-1200.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 45 publications
6
30
0
Order By: Relevance
“…The implant-related complications (including complications not requiring unplanned surgery, e.g., temporary distraction failures or painful distractions) ranged from 48 to 75% in studies with a minimum 2-year follow-up [16,24,25]. One study reported a complication rate of 0.23 per patient per year [25]. Our results show a comparable or lower complication rate of 0.18 per patient per year.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The implant-related complications (including complications not requiring unplanned surgery, e.g., temporary distraction failures or painful distractions) ranged from 48 to 75% in studies with a minimum 2-year follow-up [16,24,25]. One study reported a complication rate of 0.23 per patient per year [25]. Our results show a comparable or lower complication rate of 0.18 per patient per year.…”
Section: Discussionmentioning
confidence: 53%
“…MCGR studies with a minimum 2-year follow-up report that patients requiring unplanned surgery ranged from 39 to 75%. 92 patients combined from four studies experienced 17 cases of a nonfunctioning MCGR and 12 cases of rod fracture requiring unplanned surgery (a total of 31%) [ 15 , 16 , 24 , 25 ]. Our cohort consisting of 18 patients experienced two cases of a non-distracting MCGR after implantation and one rod fracture requiring unplanned reoperation (a total of 17%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study helps provide one explanation for the failure of internal mechanism of MAGEC rods, but the role of other failure mechanisms of MAGEC rods is yet to be explained. Given the success of material loss quantification in our study, further work can be done in different aspects, in particular to assess the contribution of material loss to the increased serum ion levels and metallosis in patients receiving MAGEC rods, which have been increasingly reported in recent studies [18][19][20].…”
Section: Discussionmentioning
confidence: 95%
“…21,47 Rod configuration and implantation Similar to TGR, dual rods are preferred over single rods for MCGR surgery. 48 Dual rods have been shown to produce increased distraction forces and to allow for differential correction. 17,19 Single rods may only be used in very thin patients without adequate soft tissue coverage and if the severe rotational and gibbus deformities preclude rod insertion.…”
Section: Anchorsmentioning
confidence: 99%